All I really need to know I learned in kindergarten : uncommon thoughts on common things - Fulghum, Robert (Boston, Mass. : G.K. Hall, 1989)
In this collection of essays, the author illustrates the idea that the most important lessons in life are the basic lessons learned in kindergarten
Keywords: Life